The Effect of Joyful Learning Strategies on Student Activeness in the Fiqh Learning Process in Class V MI - Agus Fathoni Prasetyo; Siti Nurjanah; Qoridatul Mu'awanah (Universitas Muhammadiyah Sidoarjo, 2020)
Education is an important capital for a person to live his life. The role of education is inseparable from the components of students, teachers, learning materials, learning media, learning models, and so forth. The main factors in the education described need to be improved because the progress of the civilization of a society or nation lies at the level of education. This research is also motivated by the low level of student activity during the learning process. The low student activeness is due to the way the teacher delivers the material and the educator rarely applies varied strategies in the learning process. So the learning process becomes monotonous and boring and causes students to assume that the fiqh lesson is not important and saturating, or they think it is enough to listen to the fiqh lesson as it is finished just like that, without any application. One strategy that can be used is to implement a joyful learning strategy or fun learning. This study aims to determine whether there is an influence of joyful learning strategies on student activity in the fiqh learning process especially in circumcision material at MI Miftahurrohman Senori Tuban. This type of pre-experimental research with the type of one group pretest-posttest design. The population in this study were class V students consisting of one class that was used as an experimental class with a total of 14 students and all members of the population were sampled in this study. Data collection techniques were observation, tests (pretest and posttest) and documentation. The results of the study and discussion of the t test calculations obtained that thitung = 2.197 and ttabel = 1.771. This means that thitung is greater than ttabel so it can be concluded that there is an influence of joyful learning strategies on student activeness in the learning process of fiqh in MI Miftahurrohman Senori Tuban class on circumcision material after being treated. Increased student activity is influenced by the use of learning strategies.